Can we recognise obesity clinically?. Issue 12 (2nd May 2008) - Smith, S M; Gately, P; Rudolf, M
Abstract : The aim of this study was to ascertain whether health care professionals are able to accurately identify overweight and obese children by observation alone. Eighty health care professionals were asked to view photographs of 33 children and assign each into one of six categories, ranging from "very underweight" to "obese". The health care professionals' categorisation was compared with the children's degree of adiposity based on conventional clinical criteria for BMI. The health care professionals were found to be generally poor at assessing the weight status of the children, and in particular tended to underestimate overweight and obesity in children. This study suggests that it is not appropriate to rely on informal assessment to identify obesity and highlights the need for health care professionals to be aware of their lack of accuracy in this regard.